Integrasi IoT Dalam Rantai Nilai Agribisnis: Telaah Literatur Terhadap Inovasi Dan Efisiensi Sistem Pangan - Zahraturrahmi, Zahraturrahmi -; Suardi, Tennisya Febriyanti (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2025)
This study aims to (1) find out how Internet of Things (IoT) innovations are used in agribusiness, (2) assess how they help improve the efficiency and sustainability of the food system, and (3) identify the challenges and opportunities for using IoT in modern agribusiness development. The approach used is an integrative literature review of 40 scientific articles obtained from the Scopus and Google Scholar databases. Articles were selected based on inclusion criteria, namely, in English or Indonesian, published between 2017 and 2025, and relevant to the topic of IoT integration in agribusiness or food systems. The analysis was carried out descriptively. The results of the study show that IoT integration in the agribusiness value chain has driven significant transformation, especially in terms of real-time monitoring, process automation, and data-based decision-making. This technology contributes to the implementation of precision agriculture, resource efficiency, and increased transparency across all stages of the value chain, from production to marketing. However, its implementation still faces various obstacles such as data security issues, low technological literacy, and high investment needs. Overall, IoT has great potential to increase the competitiveness and sustainability of the agribusiness sector. Therefore, policy support, training, and cross-sector collaboration are needed to optimize the use of this technology in the future.